Multifunctional ZnO/TiO2 nanoarray composite coating with antibacterial activity, cytocompatibility and piezoelectricity. Issue 10 (July 2019) - Pang, Shumin; He, Yuan; Zhong, Ru; Guo, Zhenzhao; He, Ping; Zhou, Changren; Xue, Bo; Wen, Xuejun; Li, Hong
Abstract: Metal oxides with nanostructures such as zinc oxide (ZnO), titanium dioxide (TiO2 ) have been used in biomedical fields for their multifunctional properties. In this study, ZnO/TiO2 nanoarray (nZnO/TiO2 ) coatings were prepared via hydrothermal synthesis followed by low temperature liquid phase method. The particle size of the composites were no more than 100 nm in diameter, assembled into nanoarray on the Ti substrate. In vitro antibacterial experiments showed that the maximum bacteriostatic rate could reach 99% against Staphylococcus aureus and 90% against Escherichia coli, respectively. Moreover, the nZnO/TiO2 coatings were of cytocompatibility and biocompatibility, promoting the proliferation of MC3T3-E1 and the expression of alkaline phosphatase (ALP). The piezoelectric properties of nZnO/TiO2 coatings were preliminarily investigated. The smaller the size of the composite particle was, the better the antibacterial property, biocompatibility and piezoelectric properties were. Under the stimulation of the periodic loading, the growth of MC3T3-E1 was promoted, so the secretion of ALP was. The nZnO/TiO2 composite coating with antibacterial activity, osteogenesis and intellectual stimulation would be a promising smart coating for orthopedic implants.